THE SPEECH ERRORS MADE BY EFL LEARNERS IN SPEAKING PERFORMANCE - Nuzulul Febriana (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Speaking skill is the ability to deliver and produce language through the mouth. Learners create sounds using many parts of body, including lungs, tongue, teeth, lips etc. In this globalization era, speaking skill has an important role in communication, particularly in communication English as a foreign language. When it deals to communication, learners often produce some errors in speaking performances due to inability to resolve the complexity of speech.This study aimed to investigate and identify the learners’ speech error made by EFL learners in speaking performance and it was conducted at second semester of EFL learners in speaking’s presentation. The research problem was narrated as follows: What types of speech errors made by second semester of EFL learners at University of Islam Malang in the speaking performance?The method applied was descriptive qualitative. The researcher took the population in second semester of EFL learners. The second semester of class A was the sample of this research because they were the lowest score learners among other classes. Observation, video documentation, and note as the instrument of data collection. The data were analyzed in the form of descriptive qualitative using comprehending, synthesizing, theorizing, and recontextualising. Furthermore, the data triangulation was assist to cover up the data gathered.The finding of this present study formulated that the speech errors made by EFL learners was seven items and identified into four categories, such as; shift error, perseveration error, substitution error, and anticipation error. The highest number of speech error items that made by the researcher was shift error. Otherwise, the research couldn’t find two error categories, like exchange and blend error.Based on the finding of the study, the English lecturer was suggested to create new proper strategy and invite EFL learners to be more active in the classroom learning. By reading and understanding this present research, the EFL learners were suggested to be more aware in their errors of speaking performance. Henceforth, it can be detracted the learners’ speech error in their speaking. It was also addressed for future researcher to adopt the newest version of learners’ interview or questionnaire check list as the instrument which can cover up this present study. The further researcher also suggested to do research of error in speaking performance with other different speech error categories and how to overcome that problemKeywords: Speaking, speaking performance, speech error